Effect of Feline Interferon-Omega on the Survival Time and Quality of Life of Cats with Feline Infectious Peritonitis - Ritz, Susanne; Egberink, Herman; Hartmann, Katrin (Journal of veterinary internal medicine, 2007)
There is no therapy with proven efficacy to treat cats with feline infectious peritonitis (FIP).BACKGROUNDThere is no therapy with proven efficacy to treat cats with feline infectious peritonitis (FIP).Feline interferon-omega (FeIFN-omega) prolongs survival time and increases quality of life in cats with FIP.HYPOTHESISFeline interferon-omega (FeIFN-omega) prolongs survival time and increases quality of life in cats with FIP.Thirty-seven privately owned cats were subjects of this study.ANIMALSThirty-seven privately owned cats were subjects of this study.The study was performed as a placebo-controlled double-blind trial. Feline infectious peritonitis was confirmed by histology or immunostaining of feline coronavirus (FCoV) antigen in effusion or tissue macrophages or both. The cats were randomly selected for treatment with either FeIFN-omega or a placebo. All cats received adjunctive treatment with glucocorticoids and antibiotics and passive immunization with Feliserin.METHODSThe study was performed as a placebo-controlled double-blind trial. Feline infectious peritonitis was confirmed by histology or immunostaining of feline coronavirus (FCoV) antigen in effusion or tissue macrophages or both. The cats were randomly selected for treatment with either FeIFN-omega or a placebo. All cats received adjunctive treatment with glucocorticoids and antibiotics and passive immunization with Feliserin.There was no statistically significant difference in the survival time of cats treated with FeIFN-omega versus placebo or in any other variable evaluated (with the exception of the lymphocyte count). The cats survived between 3 and 200 days (median, 9 days). There was only 1 long-term survivor (> 3 months), and the cat was in the FeIFN-omega group.RESULTSThere was no statistically significant difference in the survival time of cats treated with FeIFN-omega versus placebo or in any other variable evaluated (with the exception of the lymphocyte count). The cats survived between 3 and 200 days (median, 9 days). There was only 1 long-term survivor (> 3 months), and the cat was in the FeIFN-omega group.No effect of FeIFN-omega on survival time or quality of life could be demonstrated in this study.CONCLUSION AND CLINICAL RELEVANCENo effect of FeIFN-omega on survival time or quality of life could be demonstrated in this study.